2022
DOI: 10.3389/fped.2021.762241
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Hemoglobin Level, Oxygen Saturation and Postoperative Outcomes in Children With Cyanotic Congenital Heart Disease: A Propensity-Score Matching Analysis

Abstract: BackgroundThe optimal preoperative hemoglobin (Hb) level is difficult to define in children with cyanotic congenital heart disease (CHD) due to hypoxemia-induced secondary erythrocytosis. This retrospective study integrated preoperative Hb and pulse oxygen saturation (SpO2) using the product of Hb × SpO2 to predict postoperative outcomes in children with cyanotic CHD.Patients and MethodsChildren aged <18 years undergoing cardiac surgery with cyanotic CHD were included. The cutoff value of Hb × SpO2 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…HB could combine with oxygen to transport oxygen, and there is a relationship between hypoxia in skeletal muscle [Tseng 2021]. Previous researchers have reported that admission HB was related to many diseases, such as acute ischemic stroke, cyanotic congenital heart disease, and gestational diabetes [Liu 2022;Zhou 2021;Sissala 2022]. In this study, a significant difference also was found between survivors and nonsurvivors.…”
Section: Discussionmentioning
confidence: 53%
“…HB could combine with oxygen to transport oxygen, and there is a relationship between hypoxia in skeletal muscle [Tseng 2021]. Previous researchers have reported that admission HB was related to many diseases, such as acute ischemic stroke, cyanotic congenital heart disease, and gestational diabetes [Liu 2022;Zhou 2021;Sissala 2022]. In this study, a significant difference also was found between survivors and nonsurvivors.…”
Section: Discussionmentioning
confidence: 53%
“…Numerous limitations require consideration in this study. The retrospective design poses challenges in confirming direct causality and is susceptible to predisposition from unobserved variables like oxygen saturation and chronic hypoxemia, such as obstructive sleep apnea, heart disease, or obesity hypoventilation syndrome, which might have influenced our findings ( 26 , 28 , 29 ). Second, our hospital data could not capture the reason for anemia or polycythemia.…”
Section: Discussionmentioning
confidence: 99%